2015
DOI: 10.1080/22201181.2015.1028216
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intrathecal midazolam versus fentanyl for endoscopic urology surgery

Abstract: Background: This prospective randomized double-blind study was designed to compare the analgesic efficacy and safety of intrathecal midazolam versus fentanyl as an adjunct to bupivacaine for endoscopic urology surgery. Methods: Sixty adult ASA grade I-II patients undergoing transurethral resection of prostate or bladder tumor under spinal anesthesia were randomly allocated into three groups. Group B (control group) received 2 ml 0.5% hyperbaric bupivacaine while group BM received midazolam 2 mg and group BF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…10 Another study by Bharti et al, comparing intrathecal midazolam (2 mg) and fentanyl (25 µg) in endoscopic urological surgeries, proved that both offered similar advantages regarding duration of complete and effective analgesia postoperatively. 11 A similar comparison, performed by Elfawal et al, also confirmed the same results. 12 Several studies reported similar outcomes regarding the superiority of the analgesic effect of LA when adjuvants were added, but with various intergroup differences.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…10 Another study by Bharti et al, comparing intrathecal midazolam (2 mg) and fentanyl (25 µg) in endoscopic urological surgeries, proved that both offered similar advantages regarding duration of complete and effective analgesia postoperatively. 11 A similar comparison, performed by Elfawal et al, also confirmed the same results. 12 Several studies reported similar outcomes regarding the superiority of the analgesic effect of LA when adjuvants were added, but with various intergroup differences.…”
Section: Discussionsupporting
confidence: 78%
“…10 Also, Bharti et al, noted that regression of the sensory level to S2 segment was significantly delayed in the fentanyl and midazolam groups in comparison to the bupivacaine alone with comparable intergroup differences. 11 Duration of sensory and motor blocks was prolonged in fentanyl, nalbuphine and midazolam groups in comparison to bupivacaine alone with insignificant intergroup differences among adjuvants. These outcomes agree with other researchers who demonstrated similar outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…and in midazolam group, mean onset of sensory block was 223.6 sec. Similar values were obtained with regard to the onset of sensory block in midazolam group in the studies conducted by Nidhi Agrawal et al 11 in 2005 and Aikta Gupta et al 12 in 2008. There were no differences between the two groups with respect to the onset of block as significance value obtained from independent sample's t test was more than 0.05 (here it is 0.487).…”
Section: Discussionsupporting
confidence: 76%
“…Davoudi et al (2007) reported that a small dose of intrathecal pethidine is effective in decreasing shivering associated with spinal anaesthesia. 12 However, intrathecal opioid administration is relatively more invasive and carries risk of opioid side effects 13 .…”
Section: Introductionmentioning
confidence: 99%